Subleasing of Leased Land in Islamic Law: An Empirical Study of Ijarah Practices in Perum Kencana Asri - Arif Romdhoni (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2026)
This study aims to analyze the practice of renting back leased land to third parties in Perum Kencana Asri, Pucangan, Kartasura, Sukoharjo, from the perspective of the ijarah agreement in Islamic law. The research is motivated by the recurring phenomenon of tenants subletting leased property without explicit permission from the owner, which raises legal and ethical issues in both Islamic jurisprudence and Indonesian regulations. Using a qualitative field research approach, data were collected through in-depth interviews with homeowners, primary tenants, and third-party stall renters, supported by lease documents as secondary material. The findings show that the subletting practice fulfills the pillars and requirements of an ijarah contract, such as competent contracting parties, clear benefits, mutual consent, and agreed rental compensation, although initial permission from the owner was given only after the practice had already taken place. The research also reveals that while Indonesian law generally prohibits subleasing without the owner’s approval, Islamic jurisprudence supported by the majority of scholars and DSN-MUI Fatwa No. 112/2017 permits it as long as the owner consents and no contractual harm arises. This study contributes to the discipline by providing an empirical analysis that bridges normative muamalah principles with real community rental practices.